CURATORS ARE VULNERABLE TO BE CRIMINALIZED AND CRIMINATED IN BANKRUPTCY AND PKPU PROCESSES - Ranto Parulian Simanjuntak (Universitas Pelita Harapan, 2023)
The Curator is one of the important organs in the debt settlement process between debtors and their creditors through bankruptcy law instruments. Based on Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU), the Curator is given broad and broad duties and powers in managing and settling the assets of a bankrupt debtor. Because since being declared bankrupt by the court, the debtor has lost his right to manage his business and assets. The duties and authorities to administer the business and assets of the bankrupt debtor rest in the hands of the Curator, who works under the supervision of the Supervisory Judge. In carrying out its duties and authorities, the Curator must adhere to the provisions of the Law and the Professional Code of Ethics, namely being independent, having no conflict of interest and not handling more than 3 (three) Bankruptcy and PKPU cases. If in carrying out its duties and authorities it causes damage to the bankrupt assets, then the Curator must be legally responsible. That means, the Curator does not have the right of immunity or impunity in carrying out his duties and authorities to manage and settle bankruptcy assets in accordance with the provisions of the law. The Curator is not a public official. The Curator may be punished if his actions and decisions in administering and settling the bankrupt assets cause harm to the bankrupt assets. However, Law Number 37 of 2004 concerning Bankruptcy and PKPU does not include criteria for criminal acts and criminal sanctions for Curators. Because of this, Curators are vulnerable to being criminalized and punished.The Curator is one of the important organs in the debt settlement process between debtors and their creditors through bankruptcy law instruments. Based on Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU), the Curator is given broad and broad duties and powers in managing and settling the assets of a bankrupt debtor. Because since being declared bankrupt by the court, the debtor has lost his right to manage his business and assets. The duties and authorities to administer the business and assets of the bankrupt debtor rest in the hands of the Curator, who works under the supervision of the Supervisory Judge. In carrying out its duties and authorities, the Curator must adhere to the provisions of the Law and the Professional Code of Ethics, namely being independent, having no conflict of interest and not handling more than 3 (three) Bankruptcy and PKPU cases. If in carrying out its duties and authorities it causes damage to the bankrupt assets, then the Curator must be legally responsible. That means, the Curator does not have the right of immunity or impunity in carrying out his duties and authorities to manage and settle bankruptcy assets in accordance with the provisions of the law. The Curator is not a public official. The Curator may be punished if his actions and decisions in administering and settling the bankrupt assets cause harm to the bankrupt assets. However, Law Number 37 of 2004 concerning Bankruptcy and PKPU does not include criteria for criminal acts and criminal sanctions for Curators. Because of this, Curators are vulnerable to being criminalized and punished.